Business decision making, second edition streamlining the process for more effective results - Frankl, Milan (Gildan Audio, 2020)
How do executives make decisions' Are their decisions conscious or unconscious' Can they explain each decision they make' What tools can they use to improve their decision-making process' These are some of the questions this book addresses.During the past thirty-five years, as an entrepreneur and senior executive of several medium-sized Canadian hi-tech businesses, the author noticed that his decision-making processes were often based either on experience or on advice received from colleagues. Seldom were the decisions based on formal or informal academic-based methods.There is no substitute for years of experience in any human endeavor. However, tapping into some of the methods and lessons learned from personal experience can result in useful principles for others to follow. These principles are very useful, especially for entrepreneurs interested in building their businesses or executives looking for some additional help in acquiring a better decision-making mousetrap.